Anti-JC virus antibody titres increase over time with natalizumab treatment. (December 2015) - Raffel, J; Gafson, AR; Malik, O; Nicholas, R
Background: Anti-JC virus antibody status is a risk factor for progressive multifocal leukoencephalopathy after natalizumab treatment in multiple sclerosis. Previous studies have used a cross-sectional approach to conclude that the presence and duration of natalizumab treatment does not influence anti-JCV Ab seropositivity. Objectives: Using a longitudinal approach, we measured change in anti-JCV Ab results after natalizumab treatment. Methods: Anti-JCV Ab results ( n = 1154) from the second-generation STRATIFY JCV™ DxSelect™ test were analysed from an observational cohort of MS patients on natalizumab ( n = 485; n = 340 with repeat testing; n = 657 repeat tests on natalizumab). Results: Across sequential paired tests, seroconversion rate was greater than seroreversion rate (40/364 (11.0%) versus 18/293 (6.1%); p < 0.05). Moreover, anti-JCV Ab index increased across longitudinal paired tests ( m A–B 0.102; paired t (656) = 5.0; p < 0.0001). This magnitude of Ab level increase far exceeds that expected due to increasing age alone. Conclusion: Our data suggest that natalizumab therapy is associated with a significant and substantial increase in anti-JCV Ab index over time. Further work should focus on the underlying mechanisms of this phenomenon, and the clinical relevance to risk stratification.